Wind farm layout optimization using combined area dimensions and definite point selection techniques - Shakoor, Rabia (2016)
The current wind turbines are the biggest rotating machines on earth, operating in the lowest part of the earth boundary layer. The layout scheme of wind farms is a challenging job to researchers having many design objectives and constraints due to the multiple wake phenomenon. The far wake effect is more prominent in wind farm layout design problems than the near wake effect. At present, wind energy industry is facing major design constraints in boosting power output. Most of the existing approaches focused only on the positioning of the wind turbines within the wind farms. They did not consider the effect of the shape of wind farm area on power output. This research proposes a novel method to find the optimized dimensions of the wind farm shape where maximum area could face the free stream velocity. This is achieved by developing an area dimension method which rotates the wind farms up to 180 degree. Afterward, a novel method called Definite Point Selection (DPS) is developed to place the turbines in order to operate at their maximum efficiency, while providing the obligatory space between adjacent turbines for operation safety. The positions within the wind farm facing zero wake effect can be identified by using DPS method. It is observed that the combined area dimension and DPS techniques are more effective than the previous approaches. Jensen’s wake model is used to calculate the wake effects among wind turbines as existing literatures illustrate that the Jensen’s far wake model is a good choice acceptably for the solution of layout problem. A wind farm of 2 km x 2 km area is divided into 10 x 10 cells for case study. Three different wind scenarios i.e. constant wind speed with uniform direction (Case 1), uniform wind speed with variable direction for equal probability of occurrence (Case 2) and variable wind speed with variable direction for unequal probability of occurrence (Case 3) are considered for the application of proposed methods. The proposed layouts are simulated to place different number of wind turbines in all wind scenarios. The optimized layout operates with efficiency of 99.15%, 96.9% and 93.9% for Case 1, Case 2 and Case 3 respectively. Results show that power output of the wind farm by using the same area in different dimension has increased even with identical number of wind turbines. The proposed method is useful for onshore as well as offshore wind farms.